Peningkatan Produktivitas Kerja Guru Pada Implementasi Bimbingan Individual Di SMP Negeri 3 Muntok - Ida Safrina (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of carrying out this research is to find out: (1) The steps for implementing individual guidance by the principal for teachers to increase teacher work productivity at SMP Negeri 3 Muntok, and (2) The magnitude of the increase in teacher work productivity after implementing individual guidance developed by the school principal . This research is school action research analyzed using a qualitative approach. The research was carried out at SMP Negeri 3 Muntok in 2019. The research results obtained were: (1) The implementation of individual guidance can be developed based on the steps: (1) Guidance on developing learning models through comparative studies and follow-up planning, followed by analytical guidance SWOT; (2) Guidance on the implementation of educational administration, followed by providing direct feedback on the results of the teacher's work; (3) Advanced guidance sets reliable targets, developed through joint evaluation of program targets for other teachers who are also experiencing the same problems; (4) Guidance on how to carry out collaboration with other teachers in more depth, up to the ability to demonstrate the materials needed by other teachers; (5) Guidance on effective and efficient work strategies, which are developed through training in determining optimal quantity figures and how to measure them, namely through scoring techniques; (6) Developing motivational guidance; (7) Building independence so that teachers avoid plagiarism-based activities, and guidance in making effective plans; (8) Guidance in making effective work planning coupled with innovative aspects; (9) Encourage teachers to implement programs to increase teacher competency through seminars and workshops followed by implementation of the results of new experiences from teacher activities; (2) The implementation of individual guidance is able to increase teacher work productivity in schools by resolving teacher problems in the development and implementation of learning programs in schools.